Analisis Kedudukan Asas Keseimbangan Dalam Perjanjian Asuransi Jiwa di Indonesia - Sonya, Grace; Aldira Mara Ditta Caesar Purwanto (Lex Stricta : Jurnal Ilmu Hukum, 2026)
The principle of balance in life insurance agreements in Indonesia predominantly utilizes standard contracts. Standard contracts drafted unilaterally by insurance companies can create an imbalance of position between insurance companies with strong economic standing and policyholders in weak positions, where customers often do not understand their rights and obligations due to lack of information transparency and complexity of legal language in policies. The research method employs a normative juridical approach by analyzing relevant legislation and Constitutional Court Decision No. 83/PUU-XXII/2024. The research findings indicate that although the use of standard contracts is difficult to avoid due to operational efficiency needs, the principle of balance holds a fundamental position as a legal instrument to prevent injustice. This principle has a strong legal foundation based on Article 1320 of the Civil Code and is reflected in Law No. 40 of 2014 concerning Insurance and Law No. 8 of 1999 concerning Consumer Protection. The research concludes that the application of the principle of balance must be implemented at every stage of legal relations to ensure sustainability and contractual justice in the Indonesian life insurance industry.